Analisis Penerapan Lean Manufacturing Untuk Meminimalisir Waste Pada CV. Adelia Medika Supply - Ernawati, Nani; Utomo, Urip Prajoko Puji; Juliani, Citra; K, Kusdinar; Effendi, Muhammad Zidan; Ubaidilla, Nisfu; Ayu, Sri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to reduce time and cost wastage in the shipping department of CV Adelia Medika Supply through the implementation of Lean Manufacturing concepts. The methods used in this study include data collection through observation and interviews, and analysis using the Kanban approach. The results indicate that the implementation of Lean Manufacturing successfully reduced packaging and shipping times by up to 50%. Additionally, the procurement of a new storage warehouse and the implementation of SOPs for storage layout significantly contributed to the operational efficiency of the company. The implementation of Lean Manufacturing not only improved time and cost efficiency but also enhanced customer satisfaction and company profitability.